От мониторинга параметров - к мониторингу состояний силового трансформатора - Поляков, М.А. (Електротехніка і електромеханіка, 2011)
Modeling of conditions of power transformers by results of monitoring of its parameters is considered. The automatic model of dynamics of conditions of the power transformer, conditions of its application and diagnosing system are offered.